Potentiality of using mechanically separated meats of nile tilapia in fishburgers: Chemical, physical and sensory characterization - da Costa, Denise Pinheiro Soncini; Vinturin Gonçalves, Tania Maria [UNESP]; Conti-Silva, Ana Carolina [UNESP] (FapUNIFESP (SciELO), 2019)
Fishburgers were made with washed mechanically separated meat (MSM) from carcass and filleting by-product (both washed and unwashed) of the Nile tilapia. The proximal composition of fishburgers was different and varied according to the raw material used, as well the color parameters. Fishburgers with MSM from filleting by-product had lower hardness and springiness, and fishburger with MSM from unwashed filleting by-product had higher yield and lower reduction in thickness. The fishburgers containing MSM from filleting by-product had better sensory acceptance, due to higher color intensities (sensory), fish odor, tenderness, succulence, cohesiveness and fish flavor. The fishburger with MSM from washed carcass was the least acceptable, because of surface uniformity. This study shows the potentiality of using MSM from tilapia filleting by-product for burgers, while the formulation of fishburgers with smaller amounts of MSM from washed carcass or with added condiments can result in improved sensory acceptance and potentiality of use.
Keywords: Carcass; Filleting by-product; Sensory acceptance; Sensory profile